TEORI KEPRIBADIAN SOCIAL COGNITIVE: KAJIAN PEMIKIRAN ALBERT BANDURA PERSONALITY THEORY SOCIAL COGNITIVE: ALBERT BANDURA - Suwartini, Sri (AL-TAZKIAH : Journal of Islamic Guidance and Counseling, 2016)
The various viewpoints of personality experts apparently caused Albert Bandura to develop his investigation focus in psychology. Through Banduraâs theory developed, the social learning theory or social cognitive more refers to Skinner view about conditioning theory. Bandura looked at the existence of personality theories such as; psychoanalysis, emphasized on the strength of unconsciousness and the influence of childhood. The characteristic theory is too focused on consistency of behavior in various situations.Â  Evolution theory believed that the biological factor would not change. As well as the basic principle of behaviorism theory which regards organism as a controlled side by the rewards and punishments from the environment, he still lacks detail compared by the approach theory he developed more subtle, even significant. It was not because the basic assumption that is owned by this theory that humans have flexibility to learn about different types of behavior in different situation, and humans also have the capacity to control their life. Because according to Bandura, human was the producer and as product of social system. That basic assumption then he developed with the view that the development of human personality by the social-cognitive theory of learning acquired through observation and the existence of self-efficacy